2019
DOI: 10.1136/openhrt-2018-000856
|View full text |Cite
|
Sign up to set email alerts
|

Impact of changes in heart rate with age on all-cause death and cardiovascular events in 50-year-old men from the general population

Abstract: BackgroundResting heart rate (RHR), a known cardiovascular risk factor, changes with age. However, little is known about the association between changes in RHR and the risk of cardiovascular events. The purpose of this study was therefore to assess the impact of RHR at baseline, and the change in RHR over time, on the risk of all-cause death and cardiovascular events.DesignA random population sample of men born in 1943 who were living in Gothenburg, Sweden was prospectively followed for a 21-year period.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 27 publications
(32 reference statements)
1
36
1
1
Order By: Relevance
“…Compelling evidence exists regarding underutilization of β-blockers and failure to up-titration in CHF patients including older age (>70 years) and presence of respiratory disease [44], hypotension and polypharmacy [45], concern of side effects, contraindications, and poor experience of GPs [46] low HR and poor adherence to prescriptions [47]. Patients under β-blockers may experience adverse effectsmortality and cardiovascular events associated with high resting HR, as described by Chen et al 2019 [48]. Nevertheless, the reluctance of the clinicians to prescribe β-blockers due to potential side effects need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evidence exists regarding underutilization of β-blockers and failure to up-titration in CHF patients including older age (>70 years) and presence of respiratory disease [44], hypotension and polypharmacy [45], concern of side effects, contraindications, and poor experience of GPs [46] low HR and poor adherence to prescriptions [47]. Patients under β-blockers may experience adverse effectsmortality and cardiovascular events associated with high resting HR, as described by Chen et al 2019 [48]. Nevertheless, the reluctance of the clinicians to prescribe β-blockers due to potential side effects need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis published in the European Heart Journal, several studies focused on reducing RHR over time through the use of beta-blockers and calcium channel blockers, finding the reductions in RHR were associated with reductions in cardiovascular mortality 10 . A prominent work recently published in Open Heart observed that individuals with significant increases in RHR over time were at higher risk for all-cause and cardiovascular mortality 11 , finding every beat per minute increase was associated with a 3% higher risk for all-cause mortality, 1% higher risk for cardiovascular disease and 1% higher risk for coronary heart disease. The authors also highlighted the clinical utility in capturing trends in RHR, rather than relying on a single measure.…”
Section: Introductionmentioning
confidence: 98%
“…A body of literature has shown RHR to be an important biomarker for cardiovascular health [8][9][10][11][12][13] . A meta-analysis conducted by Zhang et al 9 , including 46 studies involving 1,246,203 patients, observed that higher RHR was independently associated with increased risk of all-cause and cardiovascular mortality after adjusting for traditional risk factors 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous biological mechanisms that show that sympathetic stimulation promotes both acute and chronic insulin resistance and may increase risk of diabetes: (1) sympathetic stimulation promotes vasoconstriction and reduces skeletal muscle blood flow that causes a reduction of glucose uptake into the skeletal muscle [18]; (2) sympathetic activation inhibits pancreatic b cells to secret insulin [19]; and (3) sympathetic overactivity induces the renin-angiotensin-aldosterone system that leads to increasing of HR and causes insulin resistance [20]. People with an increase in RHR between 50 and 60 years of age had poorer effect [21].…”
Section: Introductionmentioning
confidence: 99%